2013
DOI: 10.1177/1534484313500143
|View full text |Cite
|
Sign up to set email alerts
|

West Meets East? Identifying the Gap in Current Cross-Cultural Training Research

Abstract: The purpose of this article was to examine current cross-cultural training (CCT) research, using the lens of "East Meets West." The two research questions guiding our inquiry are (a) What are the major themes discussed in the existing CCT literature? and (b) What are the emerging issues that need to be addressed? Using the integrative literature review method, we first identified four themes: theories/ conceptual frameworks, expatriate adjustment, CCT methods, and the effectiveness of CCT. We found that previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Borrowed from the recent research on “West meets East” (Barkema, Chen, George, Luo, & Tsui, ; Nam, Cho, & Lee, ), we highlight the importance of cultural differences between East and West in terms of philosophies, cultural values, and human resource practices. Asian culture has generally been characterized by high levels of in‐group (or family) and institutional collectivism, power distance and paternalism (Arvey, Dhanaraj, Javidan, & Zhang, ).…”
Section: Literature Reviewmentioning
confidence: 85%
“…Borrowed from the recent research on “West meets East” (Barkema, Chen, George, Luo, & Tsui, ; Nam, Cho, & Lee, ), we highlight the importance of cultural differences between East and West in terms of philosophies, cultural values, and human resource practices. Asian culture has generally been characterized by high levels of in‐group (or family) and institutional collectivism, power distance and paternalism (Arvey, Dhanaraj, Javidan, & Zhang, ).…”
Section: Literature Reviewmentioning
confidence: 85%
“…A major issue not commonly reported in the literature on working abroad but which emerged as a major challenge for our respondents, was the impact of the move on individual's partner and children (Caligiuri, Hyland & Bross, 1998;Palthe, 2004;Rosenbusch & Cseh, 2012;Nam, Cho & Lee, 2014). This relates both to separation if the family remains in the home country or an inability of the accompanying family to adjust to the new environment.…”
Section: In-country Adjustment and Adaptationmentioning
confidence: 94%
“…Nam and colleagues' (2014) recent review on our current understanding of cross-cultural training has identified that there needs to be a shift from learning about culture to developing skills to manage oneself and others across cultures. If expatriate adjustment relates to the degree of psychological comfort and familiarity an individual feels in terms of the new culture, then "developing intercultural competence … is no longer just a recommendation but a requirement for responding to the challenges of globalization" (Nam et al, 2014;p.49 Direct personal agency, in which an individual can regulate him-or herself and the new environment Proxy agency, in which an individual tries to get those who with access to resources, expertise or have the power to act on their behalf to secure their desired outcomes, and Collective agency, in which an individual, recognising that a collective effort is more likely to achieve the desired result, will work with others to pool their knowledge, skills and resources, while providing mutual support.…”
Section: Study Demonstrated)mentioning
confidence: 99%
“…22 Cultural intelligence, a multifaceted individual attribute that assists a person in adapting effectively to a new cultural context, may also contribute to cross-cultural success. Adjustability, [22][23][24][25][26][27] cultural sensitivity, 28,29 self-efficacy, 30 previous international experience, 26,27,30 and family adjustment dynamics 31 also play major roles in contributing to the effective functioning of the cross-cultural professional. So, a number of factors have been identified which can help the healthcare missionary become successful; yet, many crosscultural workers are surprised by the difficulties they face once established in their cross-cultural living situations.…”
Section: Challenges Facing Healthcare Missionariesmentioning
confidence: 99%